Bandung City Firefighters’ Quality of Work Life - Silvia Maharani Hapsari; Megawati Batubara (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2022)
Working as a firefighter has high risk of accidents and high responsibility in carrying out their duties. Firefighters must have a good quality of work life to be able to provide optimal service. Quality of work life is a reflection of employees' feelings towards their work, including the impact of the work on employee welfare.This study aims to describe the quality of work life of firefighters in Bandung.This study uses a quantitative approach with a descriptive method. The population in this study were firefighters in Bandung.The sampling technique used is purposive sampling with 135 samples consisting of 109 men and 26 women. The instrument used is the Work-related Quality of Work Life Scale developed by Easton and Van Laar (2018). The results of the study showed that most firefighters had a quality of work life in the high category, specifically 83 people (63.7%), in medium category with total of 36 people (28.9%), and in the low category with total of 10 people (7.6%). The results of the different test showed that there was a significant difference between men and women in the total score of the quality of work life and a significant difference between employment status on the Job and career satisfacton dimension. The high level of quality of work life of firefighters will have an impact on increasing work productivity, job satisfaction, and commitment to the organization.